2012
DOI: 10.1177/1934578x1200701112
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Licorice Seeds with Colchicine: Changes in Seedling DNA Levels and Anthocyanin and Glycyrrhizic Acid Contents of Derived Callus Cultures

Abstract: The use of colchicine to induce polyploids increases secondary metabolite production potential and has been used for many years for the production of valuable compounds in plants. This project took advantage of this method to increase the production of secondary metabolites in licorice. For this purpose, seeds of licorice, Glycyrrhiza glabra var. glandulifera, were treated with different concentrations of colchicine for 24 hours and then cultivated in vitro. After a month, the effect of colchicine on the cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
8
1
Order By: Relevance
“…To meet the growing demand of the herbal industry, in vitro cultures could be an alternative to field-grown plants for consistent production of secondary metabolites within a short period [ 15 ]. Several reports indicate the potential of manipulating in vitro tissues to produce bioactive terpenoids, phenolics, saponins and anthocyanins [ 16 - 18 ], but any attempt to engineer efficient production of secondary metabolites requires understanding of their biosynthetic pathway(s), and our present knowledge of withanolide biosynthesis is limited to only a few genes involved in the pathway [ 10 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…To meet the growing demand of the herbal industry, in vitro cultures could be an alternative to field-grown plants for consistent production of secondary metabolites within a short period [ 15 ]. Several reports indicate the potential of manipulating in vitro tissues to produce bioactive terpenoids, phenolics, saponins and anthocyanins [ 16 - 18 ], but any attempt to engineer efficient production of secondary metabolites requires understanding of their biosynthetic pathway(s), and our present knowledge of withanolide biosynthesis is limited to only a few genes involved in the pathway [ 10 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Triploid progeny population obtained from diploid and tetraploid of Camellia tea species indicated that the catechin and caffeine levels of the triploid progenies were higher than their diploid parent and showed heterosis for caffeine and EGCG, thus allowing quantitative enhancement of some of the quality-related parameters in tea (Das et al, 2013). The ploidy level in licorice plantlets obtained from treatment with 0.08% (to induce mixoploidy [defined as presence of both diploids and polyploids in a population]) and 0.1% ( to induce tetraploidy) of colchicine demonstrated that the anthocyanin level was significantly increased in callus obtained from mixoploid plantlets whereas the amount of glycyrrhizic acid increased upon induction of polyploidization, proving an increased production of metabolites in polyploid licorice tissues (Bernard et al, 2012). In copperexposed diploid and tetraploid chamomile (Matricaria chamomilla) roots, it was demonstrated that flavonoids and phenolic acids did not differ with respect to ploidy ( al., 2010).…”
Section: Phenylpropanoidsmentioning
confidence: 99%
“…The amount of chlorophyll produced per gram leaf tissue is also affected by environmental conditions and the genetic composition of the plant [48]. Since T 4 is known to increase the total DNA content in plant cells [49], it might have enhanced synthesis of photosynthetic pigments as well.…”
Section: Effects Of the Propagation Substrate And Chemical Mutagens Omentioning
confidence: 99%
“…Warner and Gerald [50] suggested that the photosynthetic rate per unit leaf area is related to the number of photosynthetic cells per unit area. As a matter of fact, the photosynthetic rate per cell is correlated with the amount of DNA per cell, which is increased in colchicinetreated plants [49].…”
Section: Effects Of the Propagation Substrate And Chemical Mutagens Omentioning
confidence: 99%
See 1 more Smart Citation